Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests?. (14th January 2022) - Bosch, Nestor E.; McLean, Matthew; Zarco‐Perello, Salvador; Bennett, Scott; Stuart‐Smith, Rick D.; Vergés, Adriana; Pessarrodona, Albert; Tuya, Fernando; Langlois, Tim; Spencer, Claude; Bell, Sahira; Saunders, Benjamin J.; et al.
Abstract: Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata, transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems. Abstract : We demonstrate a legacy effect of an extreme marine heatwave (MHW) in the structure and functioning of a temperate reef ecosystem. The trait structure of herbivorous fishes shifted following the MHW, with novel herbivore roles supported by range‐expanding tropical fishes. This new functional structure appears to be stable 10 years after the MHW, despite returning cool conditions and winter cold spells, potentially contributing to the replacement of the formerly dominant kelp Ecklonia radiata by 'turfs' and Sargassum spp. Our study exemplifies the lasting consequences of phenotypic (trait‐mediated) changes in the nature of core ecosystem processes in changing temperate reefs.